Singin' in the Rain: A Study of Social Pressure on the Soccer Field - Mikael Priks (Center for Economic Studies and ifo Institute (CESifo), 2013)
Although social pressure may affect the behavior of individuals, it is very hard to evaluate empirically. A soccer field is an attractive testing ground in the sense that both performance and social pressure by spectators are measurable. The drawback is that the number of spectators is an endogenous variable. To solve this problem, I use pre-game precipitation as an instrument for the number of spectators at Swedish soccer games as it reduces attendance but not relative performance on the field. I find that organized home supporters manage to generate home wins. Highly skilled athletes are consequently influenced by social pressure, which can also help explain the well-known home field advantage.
Keywords: D80; J20; K40; 330; social pressure; bias; home-field advantage